Konseling Behavioral dengan Teknik Sosiodrama Melalui Lesson Study Untuk Meningkatkan Self-Succorance - Ariandani, Ni Putu Diah; Dantes, Nyoman; Dharsana, I Ketut (Jurnal Jurusan Bimbingan Konseling Undiksha, 2019)
The first objective of this study was to know the extent of effectiveness of the implementation of behavioral counseling theory by using sociodrama technique to improve self-succorance of grade VII students of SMP Lab. Undiksha Singaraja, The second objective of this study was to know the difference of self-succorance between the students who were given behavioral counseling by using sociodrama technique and the students who were not given behavioral counseling by sociodrama technique on grade VII of SMP Lab.Undiksha Singaraja. This was an experimental study with non-equivalent pre-test post-test control group design. The population of this study was the students of grade VII of SMP Lab. Undiksha. The study sample was taken by using random sampling technique, in which it was found that 103 students had moderate and low self-succorance. From the 103 students who were selected as members of the sample, it was randomly selected 1 class as the experimental group and the other 1 class as the control group. The data collection method of self-succorance in the study used the obsevation method, interview, diary and self-cycles questionnaire of Likert scale. The analysis method of the hypothesis test used was the t-tes. The results of this study indicated that there was effectiveness of the implementation of Behavioral Counseling by using Sociodrama technique to improve self-Succorance of grade VII students ofÂ  SMP Lab. Undiksha, and there was a difference of self-Succorance between the students who were given behavioral counseling by using sociodrama technique and the students who were not given.Keywords: Behavioral counseling, sociodrama technique, self-succoranc